Analisis Wacana Kritis Norman Fairclough pada Pemberitaan Pelecehan Pasien oleh Oknum Perawat RSUD Majene - Abadi, Totok Wahyu (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This abstract provides a good overview of the objectives and findings of the study on reporting patient abuse by unscrupulous nurses at Majene Regional Hospital. This study raises the issue of ideological construction and power relations in the reporting of patient abuse cases by unscrupulous nurses at Majene Regional Hospital, as well as its impact on public opinion and case resolution. This study uses the Critical Discourse Analysis (CDA) approach developed by Norman Fairclough. Data were collected through analysis of news texts from online media, focusing on the language and framing used in the reporting. The study results show that the reporting represents the hegemonic ideology of neoliberalism and creates an unbalanced power relationship between patients and hospitals. The reporting tends to discredit patients and ignore their voices, which has implications for negative public opinion towards victims. This study concludes that the mass media has an important role in shaping public perception and resolving patient abuse cases. Therefore, it is recommended that the media be more objective and sensitive in reporting sensitive cases, and give voice to victims to encourage fairer and more accurate resolutions.